2006
DOI: 10.1021/ja057776q
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Replacement of Y356 with 3,4-Dihydroxyphenylalanine in the β2 Subunit of E. coli Ribonucleotide Reductase

Abstract: E. coli ribonucleotide reductase (RNR), composed of the homodimeric subunits alpha2 and beta2, catalyzes the conversion of nucleotides to deoxynucleotides via complex radical chemistry. The radical initiation process involves a putative proton-coupled electron transfer (PCET) pathway over 35 A between alpha2 and beta2. Y356 in beta2 has been proposed to lie on this pathway. To test this model, intein technology has been used to make beta2 semi-synthetically in which Y356 is replaced with a DOPA-amino acid. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
155
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(171 citation statements)
references
References 16 publications
15
155
1
Order By: Relevance
“…RNR is inactivated by 0.5 eq of F 2 CDP/␣, as a consequence of altering the affinity of its two subunits and generating an asymmetric interaction within this complex. Recent studies using ␣ and ␤ substituted site specifically with unnatural amino acids have also been interpreted to suggest an asymmetry within the active RNR complex (19,20). Our results suggest that the paradigm of a 1:1 symmetrical complex between the two subunits of RNR must be re-evaluated.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…RNR is inactivated by 0.5 eq of F 2 CDP/␣, as a consequence of altering the affinity of its two subunits and generating an asymmetric interaction within this complex. Recent studies using ␣ and ␤ substituted site specifically with unnatural amino acids have also been interpreted to suggest an asymmetry within the active RNR complex (19,20). Our results suggest that the paradigm of a 1:1 symmetrical complex between the two subunits of RNR must be re-evaluated.…”
Section: Discussionmentioning
confidence: 53%
“…␤ is a homodimer that houses the diferric-tyrosyl radical (Y • ) required for initiating nucleotide reduction on ␣. Current evidence suggests that there is one Y • and 2 di-iron clusters/␤2 (19,20). The interactions between ␣ and ␤ are weak (K d of 0.2 M) in the absence of nucleotide (21).…”
mentioning
confidence: 99%
“…The E. coli RNR is active as an α2β2 complex and nucleotide reduction is initiated by a long-range proton-coupled electron transfer (PCET) process in which Y 122 • in β2 reversibly oxidizes C 439 in α to a thiyl radical through a proposed pathway (Y 122 → W 48 → Y 356 within β to Y 731 → Y 730 → C 439 within α, Figure 1). 4,5 Our studies have shown that this process is masked by a rate-limiting conformational change (or changes) and that the conformational change is initiated by the binding of the substrate and allosteric effector to α 6-9. Conformational changes thus mask the PCET process.…”
Section: Introductionmentioning
confidence: 97%
“…This peptide contains the 20 C-terminal residues of β2, including both the binding determinant for β2 to α2 and a key tyrosine residue at the N terminus of the peptide. This tyrosine residue is in a position analogous to Y356 in β2, which facilitates radical transport at the α2∶β2 interface (22). By appending a photooxidant (PO) to this peptide (PO-Y-βC19), the equivalent of •Y356 (•Y-βC19) can be photochemically generated.…”
mentioning
confidence: 99%